2018
DOI: 10.1186/s12864-018-4852-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome alteration in Phytophthora infestans in response to phenazine-1-carboxylic acid production by Pseudomonas fluorescens strain LBUM223

Abstract: BackgroundPhytophthora infestans is responsible for late blight, one of the most important potato diseases. Phenazine-1-carboxylic acid (PCA)-producing Pseudomonas fluorescens strain LBUM223 isolated in our laboratory shows biocontrol potential against various plant pathogens. To characterize the effect of LBUM223 on the transcriptome of P. infestans, we conducted an in vitro time-course study. Confrontational assay was performed using P. infestans inoculated alone (control) or with LBUM223, its phzC- isogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(72 reference statements)
0
16
0
1
Order By: Relevance
“…Transcriptome indicated that DEGs were significantly enriched in oxidoreductase activity (acting on paired donors, with incorporation or reduction of molecular oxygen) at the MF level. The transcriptome of Phytophthora infestans treated with PCA had also indicated that DEGs related with oxidoreduction activity were significantly enriched ( Roquigny et al, 2018 ). For instance, the gene of eburicol 14 alpha-demethylase was significantly down-regulated by PCA ( Supplementary Tables 8 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome indicated that DEGs were significantly enriched in oxidoreductase activity (acting on paired donors, with incorporation or reduction of molecular oxygen) at the MF level. The transcriptome of Phytophthora infestans treated with PCA had also indicated that DEGs related with oxidoreduction activity were significantly enriched ( Roquigny et al, 2018 ). For instance, the gene of eburicol 14 alpha-demethylase was significantly down-regulated by PCA ( Supplementary Tables 8 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of amino acid content was associated also with the downregulation of amino acid transporters in tagatose-incubated P. infestans . Similarly, the downregulation of amino acid transporter genes was previously linked to P. infestans growth inhibition caused by Pseudomonas fluorescens LBUM223 ( Roquigny et al, 2018 ), indicating strong correlations between sugar metabolism, amino acid metabolism, amino acid transport and P. infestans growth.…”
Section: Discussionmentioning
confidence: 67%
“…have been found to be effective against numerous plants pathogenic organisms, including bacteria, fungi, and oomycetes, such as the causal agent of the bacterial blight of rice, and the oomycetes P. infestans [45,46]. Ye et al [46] used transcriptomics to exploit the alteration in P. infestans in response to phenazine-1-carboxylic acid production by P. fluorescens , and the transcriptome analysis provided a better understanding of the molecular mechanisms, which might in turn contribute to developing and optimizing a biocontrol strategy against the late blight of potato. Transcriptomic analyses implied that the percentages of all P. infestans ’ genes significantly changed due to P. fluorescens, and exogenically applied PCA increased as time progressed, from 50 to 61% and from to 32 to 46%.…”
Section: Resultsmentioning
confidence: 99%